2021
DOI: 10.1590/1678-9865202134e200263
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise attenuates the effects of ovariectomy and sedentarism on body composition and food intake in female rats

Abstract: Objective To evaluate the impact of low to moderate aerobic exercise and ovariectomy on body composition and food consumption in female rats. Methods Forty adult Wistar female rats (age: 23 weeks; body weight: 275.2±3.6g; mean±SEM) were divided into 4 groups (n=10): laparotomy-sedentary; laparotomy-exercised; ovariectomy-sedentary; and ovariectomy-exercised. The exercised groups were submitted to a treadmill running program (16m/min; 30min/day, 5 days/week), for 8 weeks. Body weight and food consumption were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…Also, the results showed that body mass and AT + DE groups, in which food intake was also the least in the 8th and 10th weeks, suggesting that body mass loss may be associated with energy expenditure with performing exercise and hence food intake may also decrease. In agreement with previous studies, AT can decrease food intake and increase energy consumption (Baek et al, 2020;Franco et al, 2021). Our results support the findings of Baek et al who reported that the AT + HFD (6 weeks, 15-20 m/min, 30-60 min) group was lower body mass in obese rats compared with the obese control group (Baek et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Also, the results showed that body mass and AT + DE groups, in which food intake was also the least in the 8th and 10th weeks, suggesting that body mass loss may be associated with energy expenditure with performing exercise and hence food intake may also decrease. In agreement with previous studies, AT can decrease food intake and increase energy consumption (Baek et al, 2020;Franco et al, 2021). Our results support the findings of Baek et al who reported that the AT + HFD (6 weeks, 15-20 m/min, 30-60 min) group was lower body mass in obese rats compared with the obese control group (Baek et al, 2020).…”
Section: Discussionsupporting
confidence: 93%